Examination of Faculty of Education Students' Online Learning Self-Efficacy Perceptions, Satisfaction with Online Courses and Participation in Online Courses - Gül, Ayşe; Tuncer, Murat; Yılmaz, Ömer (Mustafa KAHYAOĞLU, 2024)
In this study, education faculty students' satisfaction with online courses, their participation in online courses, and their online learning self-efficacy perceptions were investigated. The sample of the research consists of students from Fırat and Harran University faculty of education. The data of the research were collected through online student participation scale, online learning self-efficacy scale and online student satisfaction scales. Comparative tests were used to analyze the data of this research, which was conducted according to the relational screening method. According to the data obtained as a result of the research, a significant difference was found according to the university, department and frequency of participation in online courses. Additionally, it was determined that there were significant and positive relationships between online course participation, online learning self-efficacy, and online student satisfaction. The frequency of students' participation in online courses caused a significant difference in opinion in all dimensions of the data collection tools. These common findings reveal the importance of experience in online courses. Increasing the frequency of participation in online courses may encourage students to adapt and participate in distance education environments. Distance education should not be neglected due to its technological infrastructure and the fact that it is one of the main options that can be used in times of crisis. It is thought that it would be beneficial to conduct some elective courses as distance education so that students do not forget the experiences they have gained in these environments.

Bu araştırmada eğitim fakültesi öğrencilerinin çevrimiçi derslere yönelik memnuniyetleri, çevrimiçi derslere katılımın durumları ve çevrimiçi öğrenme öz yeterlik algıları araştırılmıştır. Araştırmanın örneklemini Fırat ve Harran Üniversitesi eğitim fakültesi öğrencileri oluşturmaktadır. Araştırmanın verileri çevrimiçi öğrenci katılım ölçeği, çevrimiçi öğrenme öz-yeterlik ölçeği ve çevrimiçi öğrenci memnuniyet ölçekleri aracılığıyla toplanmıştır. İlişkisel tarama yöntemine göre yürütülen bu araştırmanın verilerin çözümlenmesinde karşılaştırmaya dayalı testler kullanılmıştır. Araştırma sonucunda elde edilen verilere göre öğrenim görülen üniversite, bölüm ve çevrimiçi derslere katılım sıklığına göre anlamlı fark bulunmuştur. Ayrıca çevrimiçi derslere katılım, çevrimiçi öğrenme öz-yeterliği ve çevrimiçi öğrenci memnuniyeti arasında anlamlı ve pozitif ilişkiler olduğu belirlenmiştir. Öğrencilerin çevrimiçi derslere katılma sıklıkları veri toplama araçlarının tüm boyutlarında anlamlı düzeyde görüş farkına neden olmuştur. Bu ortak bulgular çevrimiçi derslerde deneyimin önemini ortaya koymaktadır. Çevrimiçi derslere katılım sıklığının artması öğrencilerin uzaktan öğretim ortamlarına uyumları ve katılımları konusunda onları teşvik edebilecektir. Uzaktan öğretim gerek teknolojik altyapısı ve gerekse kriz dönemlerinde başvurulabilecek başlıca seçeneklerden biri olması nedeniyle ihmal edilmemeli, öğrencilerin bu ortamlarda edindikleri tecrübelerini unutmamaları için bazı seçmeli derslerin uzaktan öğretim şeklinde yürütülmesinin yararlı olacağı düşünülmektedir.
Eğitim Fakültesi Öğrencilerinin Çevrimiçi Öğrenme Öz-Yeterlik Algıları, Çevrimiçi Derslere Yönelik Memnuniyetleri ve Çevrimiçi Derslere Katılım Durumlarının İncelenmesi
Keywords: Curriculum and Instration (Other); Eğitim Programları ve Öğretim (Diğer)